Characterization of Solution-Phase Drug-Protein Interactions by Ultrafast Affinity Extraction - Beeram, Sandya R. (Methods, 2018)
A number of tools based on high-performance affinity separations have been developed for studying drug-protein interactions. An example of one recent approach is ultrafast affinity extraction. This method has been employed to examine the free (or non-bound) fractions of drugs and other solutes in simple or complex samples that contain soluble binding agents. These free fractions have also been used to determine the binding constants and rate constants for the interactions of drugs with these soluble agents. This report describes the general principles of ultrafast affinity extraction and the experimental conditions under which it can be used to characterize such interactions. This method will be illustrated by utilizing data that have been obtained when using this approach to measure the binding and dissociation of various drugs with the serum transport proteins human serum albumin and alpha(1)-acid glycoprotein. A number of practical factors will be discussed that should be considered in the design and optimization of this approach for use with single-column or multi-column systems. Techniques will also be described for analyzing the resulting data for the determination of free fractions, rate constants and binding constants. In addition, the extension of this method to complex samples, such as clinical specimens, will be considered.